Agricultural waste as a sustainable source for nanoparticle synthesis and their antimicrobial properties for food preservation - Flores-Contreras, Elda A.; González-González, Reyna Berenice; Pablo Pizaña-Aranda, José Juan; Parra-Arroyo, Lizeth; Rodríguez-Aguayo, Arath A.; Iñiguez-Moreno, Maricarmen; González-Meza, Georgia María; Araújo, Rafael G.; Ramírez-Gamboa, Diana; Parra-Saldívar, Roberto; Melchor-Martínez, Elda M. (Frontiers in Nanotechnology, 2024)
Traditional agriculture from cropping to harvesting is contributing to climate change by increasing global greenhouse emissions. Circular economy approaches and biorefinery technologies based on the reuse, recycling, and remanufacturing might result in the valorization of wastes that consequently would avoid environmental pollution. Nanoparticles synthesis using bio-waste such as stems, leaves, seeds, pulp, stubble, and bagasse is considered a green approach with low energy consumption, and low-cost production. Characteristics of raw materials influence the final application of nanoparticles in edible coatings, and films. Therefore, the preparation of nanoparticles based on cellulose, pectin, metal (titanium oxide, silver, zinc oxide), or silica are considered organic, inorganic, or hybrid nanocomposites, are resulted in several benefits including shelf-life extension and broad-spectrum antimicrobial properties by its capacity to encapsulate active compounds that greatly improve food preservation. For considering agro-waste-based nanoparticles in food, challenges in homogenization and synthesis, yield, and toxicity are mainly described. Therefore, this review examines the employment of agro-industrial waste for the development of sustainable nanoparticles and their synthesis methods (top-down and bottom-up). Moreover, it discusses their incorporation and role in active edible coatings and films by highlighting their bioactive properties, mechanisms of action, and applications in food group preservation.